Clinical features and outcomes of hospitalized adults with sickle cell disease: A case series (Indian Journal of Case Reports, 2018)
The severity of sickle cell disease may vary from asymptomatic to severe form including episodes of painful events and severe anemia. This hospital-based study was carried out to study the incidence of different clinical signs and symptoms in patients with sickle cell disease during hospitalization. Forty patients with sickle cell disease were included in the study. Hematological and clinical parameters were analyzed in each patient. Majority of the patients had episodes of painful events (65.0%), followed by fever (42.5%) and jaundice (32.5%). Fourteen patients had infection including malaria (6 patients), urinary tract infection (4 patients), septicemia (2 patients), pneumonia (1 patient), and acute calculous cholecystitis (1 patient) and 2 patients died. Patients with infection had lower hemoglobin level compared to patients without infection. Infections in these patients lead to higher morbidity and mortality rate. An early choice of antibiotics for infections along with supportive therapy for sickle cell disease can reduce the disease severity and save valuable life.